Fret: Extending DNA‐Based Molecular Photonic Wires with Homogeneous Förster Resonance Energy Transfer (Advanced Optical Materials 3/2016). Issue 3 (March 2016) - Díaz, Sebastián A.; Buckhout‐White, Susan; Ancona, Mario G.; Spillmann, Christopher M.; Goldman, Ellen R.; Melinger, Joseph S.; Medintz, Igor L.
Abstract : Molecular photonic wires (MPWs) position dyes using DNA and utilize Förster resonance energy transfer (FRET) to direct photonic energy. However, available donor–acceptor dyes limit the size of current MPWs. On page 399, I. L. Medintz and co‐workers show that homoFRET between identical dyes can provide zero loss but with random directionality. HomoFRET is extended up to five steps in the schematic model constructs with only ≈50% energy transfer loss by accessing DNA modularity. The cover image was designed by Robert Gates.